Progress update on the AgDataHub KAOP Data Dashboard - Akshatha, Annaiah (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
AICCRA Kenya initiative has been deploying sophisticated digital platforms and tools to enhance the use of CIS. The overarching objectives of these digital platforms is to provide customized digital advisories that help mitigate climate risks and enhance decision-making for farmers and stakeholders. At the heart of this initiative is the creation of a national-scale AgDataHub, jointly managed by the Kenya Meteorological Department (KMD)3 and the Kenya Agricultural & Livestock Research Organization (KALRO)4. AgDataHub-KAOP serves as a central repository, seamlessly integrating data from diverse sources with varying spatial and temporal resolutions. This integration enables the platform to deliver tailored, actionable insights aligned with Kenya's administrative divisions. By streamlining data management and optimizing resources, AgDataHub-KAOP significantly reduces the costs and efforts associated with traditional advisory systems. This approach ensures the delivery of precise, data-driven recommendations for both crop and livestock management, empowering farmers to adapt to climate variability and improve productivity.